Preservation of the Musical Instruments: Katambung , Garantung, Rabab, Sape and Kecapi in Central Kalimantan - Jonathan, Jonathan; Darma, Wika Dwi; Timotius, Frenky Albert; Sintalegawa, Jasmine Ambun; Munthe, Yesyurun (Harmonia : Journal of Music and Arts, 2023)
The problem in this research is the lack of research that shows traditional musical instruments in Central Kalimantan in the form of visualization (images) and elaboration with culture, maintenance space and also religion, which is basically applicable and useful for the maintenance of property, culture, philosophical values contained therein. This research method is qualitative research with data search through visualization of images or camera shots of the authors directly to the source of traditional musical instruments in Palangka Raya. The results show that diversity, Indonesianness through gotong royong, instrument maintenance, culture and religion are inextricably intertwined as a space for diversity and religiosity and at the same time as a further elaborative space to explore musical instruments with something that enriches art.